Stress Distribution and Rib Reinforcement Design in Konstruksi Sarang Laba-Laba (KSLL) Foundations Using the Winkler Method - Akbar Kurnia; Andriani Andriani; Abdul Hakam (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2026)
Previous studies on Konstruksi Sarang Laba-Laba (KSLL) foundations have primarily focused on bearing capacity and overall foundation performance, while limited attention has been given to soil–structure interaction, stress distribution, and reinforcement design of KSLL ribs using the Winkler method. This study investigates the stress distribution in KSLL foundation ribs and determines the corresponding reinforcement requirements under different subgrade conditions. A numerical modeling approach was employed using a structural analysis program to simulate KSLL foundations on three soil categories—soft, medium, and stiff soils—with three rib/column connector dimensions of 30 × 30 cm, 50 × 50 cm, and 80 × 80 cm. The analysis was based on the modulus of subgrade reaction (Ks) to represent Winkler-type foundation springs. The results show that Ks increases with soil stiffness, indicating stronger subgrade support in stiffer soils. Soft soil consistently produced the highest normal stress, shear stress, and settlement, followed by medium and stiff soils. The ratio of normal stress between soft and stiff soils ranged from 1.5 to 3.0, while the shear stress ratio ranged from 1.4 to 2.0 at support zones and 1.6 to 1.9 at span regions. The effect of column-size variation on normal stress was relatively limited, although larger column dimensions reduced shear stress at supports by improving force distribution. The required main reinforcement increased with normal stress, reaching 7–8 bars in soft soil, 6 bars in medium soil, and 5–6 bars in stiff soil. Shear reinforcement spacing decreased as shear demand increased, with minimum spacing of 110 mm in soft soil, 150 mm in medium soil, and 260 mm in stiff soil. These findings demonstrate the importance of incorporating soil–structure interaction, subgrade stiffness, and rib-specific reinforcement design in KSLL foundation analysis to achieve safer and more efficient shallow foundation design.